2004
DOI: 10.1128/ec.3.1.100-107.2004
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Saccharomyces cerevisiae Mpk1 Mitogen-Activated Protein Kinase Pathway to Increases in Internal Turgor Pressure Caused by Loss of Ppz Protein Phosphatases

Abstract: The Mpk1 pathway of Saccharomyces cerevisiae is a key determinant of cell wall integrity. A genetic link between the Mpk1 kinase and the Ppz phosphatases has been reported, but the nature of this connection was unclear. Recently, the Ppz phosphatases were shown to be regulators of K ؉ and pH homeostasis. Here, we demonstrate that Ppz-deficient strains display increased steady-state K ؉ levels and sensitivity to increased KCl concentrations. Given these observations and the fact that K ؉ is the major determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 31 publications
4
141
0
4
Order By: Relevance
“…This mutant has been previously shown to act in a dominant-negative manner to block the ubiquitination and degradation of CHIP substrates, such as the glucocorticoid receptor (36) and the cystic-fibrosis transmembrane conductance regulator (47). As expected from the above data, expression of Hsp70 greatly reduces the steady-state levels of T7-DLK in transfected cells (Fig.…”
Section: Chip Is Required For Hsp70-mediated Degradation Of Dlk-supporting
confidence: 73%
“…This mutant has been previously shown to act in a dominant-negative manner to block the ubiquitination and degradation of CHIP substrates, such as the glucocorticoid receptor (36) and the cystic-fibrosis transmembrane conductance regulator (47). As expected from the above data, expression of Hsp70 greatly reduces the steady-state levels of T7-DLK in transfected cells (Fig.…”
Section: Chip Is Required For Hsp70-mediated Degradation Of Dlk-supporting
confidence: 73%
“…In addition, the caffeine and CFW sensitivities of a strain lacking the Slt2 MAP kinase were also alleviated. The observation that the presence of the CaPpz1 protein can, at least in part, reverse the effects of the absence of ScPpz1 or mimic its overexpression with respect to both cation homeostasis and cell wall integrity is coherent, since it has been shown that these two phenotypes are interrelated (Merchan et al, 2004). The partial complementation of the Sch.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ScPPZ1 suppresses the lytic phenotype of an slt2 mutant, whereas deletion of the ScPPZ1 gene or inhibition of its phosphatase activity results in a phenotype additive to that of the slt2 strain (de Nadal et al, 1998;Lee et al, 1993). The functional interaction between ScPpz1 and the CWI pathway has been explained on the basis of the combination of increased internal turgor pressure in Ppz-deficient strains and cell wall instability observed in strains lacking Slt2 (Merchan et al, 2004). Therefore, in budding yeast, the Ppz proteins play key roles in cation homeostasis, which is likely to affect cell cycle regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally similar to a RING finger domain, U-box-containing proteins are a third group of ubiquitin ligases with E3 activity that direct ubiquitylation of chaperone protein complex substrates, leading to increased degradation by the proteasome (24,26,48). CHIP was shown to promote ubiquitylation and degradation through the proteasome of GR (31), AR (13), and other proteins (26,49), including ErbB2/Neu (50,51). However, it was previously suggested that the predominant effect of CHIP on AR is inhibition of protein folding and reduced degradation (13).…”
Section: Discussionmentioning
confidence: 99%